2011
DOI: 10.1590/s0103-84782011005000072
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de progênies de meios-irmãos do composto Isanão VF-1 de milho na safra e safrinha

Abstract: Seleção de progênies de meios-irmãos do composto Isanão VF-1 de milho na safra e safrinha.Ciência Rural, v.41, n.6, jun, 2011. Ciência Rural, Santa Maria, v.41, n.6, p.947-953, jun, 2011 41, 0.86, -13.03, 9.54 and 16.12% for plant height, ear height, lodged and broken plants, prolificacy and grain yield, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
2
1
1
Order By: Relevance
“…The estimates were, however, greater for PH and about the same for EH in relation to 45 estimates summarized by Hallauer & Miranda Filho (1988). Estimates higher than those herein observed were found by Candido et al (2011) in the population Isanão (a brachytic composite) in which the higher variability may be the result of different expression of the brachytic gene (br 2 ) in the homozygous state in different genotypes. For PH the estimates also were very smaller than the average (579.3 cm 2 , over three locations) reported by Kist et al (2010).…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…The estimates were, however, greater for PH and about the same for EH in relation to 45 estimates summarized by Hallauer & Miranda Filho (1988). Estimates higher than those herein observed were found by Candido et al (2011) in the population Isanão (a brachytic composite) in which the higher variability may be the result of different expression of the brachytic gene (br 2 ) in the homozygous state in different genotypes. For PH the estimates also were very smaller than the average (579.3 cm 2 , over three locations) reported by Kist et al (2010).…”
Section: Resultscontrasting
confidence: 87%
“…However, the use of half-sib families has been commonly used for that purpose in Brazil (VENCOVSKY et al, 1988). Several other reports have corroborated this fact (CARVALHO et al, 2007;ANDRADE;MIRANDA FILHO, 2008;SOUZA et al, 2009;LIMA NETO;SOUZA JÚNIOR, 2009;FALUBA et al 2010;KIST et al, 2010;CANDIDO et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
“…These estimates were similar and, in some cases, higher than those in other maize breeding studies involving half‐sib progenies (Berilli et al., 2013; Candido, Andrade, Garcia, Gonçalves, & Amaral Júnior, 2011; Carvalho & Souza, 2007; Carvalho, Leal, Santos, & Souza, 2003; Faluba et al., 2010; Paterniani, Guimarães, Bernini, & Gallo, 2015). It is important to highlight that the estimates of the genetic parameters that were obtained through different assays are difficult to compare due to the peculiarities of each assay, such as the type of progeny used, the number of environments, and the number of replications (Hallauer et al., 2010).…”
Section: Resultssupporting
confidence: 76%
“…The Mulamba & Mock index also provided the highest magnitudes of predicted gains for most traits with the use of economic weights assigned in popcorn (Santos et al, 2007;Freitas Júnior et al, 2009;Freitas Júnior et al, 2013). Candido et al (2011), reported that the most appropriate proportional gains for the set of traits were obtained by the economic weights assigned with the use of the Mulamba & Mock index in corn. Although the Mulamba & Mock index allowed obtaining satisfactory gains for the studied traits by using economic weights assigned, based on the premise of Cruz (1990) in plant breeding, economic weights assigned are difficult to be established.…”
Section: Estimates Of Genetic Gains By Selection Indexmentioning
confidence: 99%